An Evaluation of Student Outcomes in Interdisciplinary STEM Activities: An Example of Using STEM Rubrics - Dönmez, İsmail; Gülen, Salih (My University, 2021)
The aim of this research is to evaluate the achievements of sixth-grade students in interdisciplinary STEM education with STEM rubrics. A mixed research method was used in the research. A homogeneous sample was used in the study. The research was conducted with $6^{th}$ grade students in a public school in the Eastern Anatolia Region in the 2018-2019 academic years. Seventyseven students who participated in the STEM activity in accordance with the voluntary principle participated in the study. Qualitative data were collected with a structured interview form. The table-graphic drawing form was used in collecting quantitative data. In the analysis of the data, descriptive analysis, frequency, and percentage values were used. The findings showed that the majority of participants participating in interdisciplinary STEM education defined the constant velocity movement as the unchanged form along the way. In addition, it was determined that a small number of students were under the misconception of perceiving events such as zero resultant force acting on an object, stopping or accelerating a car as constant velocity motion. It was determined that the participants mostly focused on the car example while defining the constant velocity movement. It has been determined that the participants' ability to create graphics using table data is at a good level. It indicatesthat the use of rubrics in assessment practices in STEM education is an application that can be used in the assessment of student outcomes.

Bu araştırmanın amacı disiplinler arası STEM eğitiminde altıncı sınıf öğrencilerinin kazanımlarının STEM rubrikleri ile değerlendirilmesidir. Araştırmada karma araştırma yöntemi kullanılmıştır. Araştırmada benzeşik (homojen) örneklem kullanılmıştır. Araştırma 2018-2019 eğitim öğretim yılında Doğu Anadolu Bölgesindeki bir devlet okulunda 6. sınıf öğrencileri ile yürütülmüştür. Araştırmaya gönüllülük ilkesine bağlı olarak STEM etkinliğine katılan 77 öğrenci katılmıştır. Nitel veriler tam yapılandırılmış görüşme formu ile toplanmıştır. Nicel verilerin toplanmasında tablo-grafik çizim formu kullanılmıştır. Verilerin analizinde betimsel analiz ile frekans ve yüzde değerleri kullanılmıştır. Bulgulara disiplinler arası STEM eğitimine katılan katılımcıların, büyük bir çoğunluğunun sabit süratli hareketin yol boyunca suretin değişmemesi olarak tanımladıklarını göstermiştir. Ayrıca az sayıda öğrencinin bir cisme etki eden bileşke kuvvetin sıfır olması, bir arabanın durması veya hızlanması gibi olayların da sabit süratli hareket olarak algıladıkları yanılgısında oldukları belirlenmiştir. Katılımcıların sabit süratli hareketi tanımlarken çoğunlukla araba örneği üzerinde durdukları belirlenmiştir. Katılımcıların tablo verilerini kullanarak grafik oluşturma durumlarının iyi düzeyde olduğu tespit edilmiştir. STEM eğitiminde değerlendirme uygulamalarında rubriklerin kullanımının öğrenci kazanımlarının değerlendirilmesinde kullanılabilecek bir uygulama olduğunu göstermektedir.
Disiplinlerarası STEM Etkinliklerinde Öğrenci Çıktıları Üzerine Bir Değerlendirme: STEM Rubrik Kullanma Örneği